MENINGKATKAN PEMAHAMAN TENTANG ASPEK HUKUM PERKAWINAN CAMPURAN BEDA KEWARGANEGARAAN: BERDASARKAN HUKUM INDONESIA DAN JEPANG - Abrianti, Sharda; Sugiastuti, Yunita; Saleh, Rosdiana; Supartono, Sugeng; Kerti, Renti Maharaini (Jurnal AKAL: Abdimas dan Kearifan Lokal, 2024)
Mixed marriages between spouses of different nationalities present a number of legal issues. As mixed marriages involve two different legal systems, it is important to understand which system applies. This understanding is important for the diaspora of Indonesians in Japan, given that the number of Indonesian citizens in Japan continues to increase, according to data from the Japanese Ministry of Home Affairs and Communications. This situation increases the potential for mixed marriages between Indonesian and Japanese citizens. This community service activity aims to provide legal insight on how to determine the applicable law and the conditions for mixed marriages. The method employed in this legal counselling is descriptive. Answers to questions asked are based on legislation and principles of private international law. Legal counselling on the legal aspects of mixed marriages for the Indonesian diaspora community in Japan can be said to be effective and appropriate. The participants indicated that there had been no previous legal counselling on the subject of mixed marriages, particularly in the context of comparing Indonesian and Japanese laws. They expressed hope that further legal counselling activities could be conducted via Zoom facilities on other legal issues.